The United States and a rising China : strategic and military implications - Khalilzad, Zalmay (RAND, 1999)
China has been embarked on a process of reform and modernization that has led to unprecedented economic development. The goal is to make China a developed country, which would, among other things, raise the standard of living and prepare the base for a strong military. The Chinese leadership considers good relations with the United States to be strongly advisable, if not absolutely necessary, but sovereignty concerns (especially with regard to Taiwan) could cause tensions in the Sino-U.S. relationship. China could emerge, by 2015, as a formidable power, one that might offer an alternative to the current U.S. role as the region's preferred security partner and its ultimate security manager. At present, the best U.S. response appears to be a combination of engagement and containment, a "congagement" policy that would continue to try to bring China into the current international system while both preparing for a possible Chinese challenge to it and seeking to convince the Chinese leadership that a challenge would be difficult and extremely risky to pursue